جريمة تبييض الأموال في التشريع الجزائري - صافة, خيرة (جامعة الوادي.University eloued, 2018)
إذا اعتبرت عملية تحقيق الرفاهية الاقتصادية والاجتماعية أمرا أساسيا لكل المجتمعات، وتعمل الدول ببذل جهود لتحقيق ذلك، فبالمقابل تعد الجريمة من أهم العوامل السلبية التي تعيق تلك الجهود في سبيل تحقيق التنمية، وبما أن ظاهرة تبييض الأموال تعد من أهم العوامل التي تتسبب في إعاقة عملية التنمية لارتباطها الشديد بالأنشطة الاجتماعية بمختلف أنواعها، والاقتصادية بالدرجة الأولى، أصبح من الضروري تسليط الضوء عليها. إذ أن هذه الجريمة لها مخاطر اقتصادية واجتماعية وسياسية على المستويين الدولي والوطني، أي أن مجال تأثيرها السلبي لا يقتصر على دولة واحدة بل إن تأثيرها ذو بعد عالميAs long as the process of achieving economic and social well-being is considered essential for all societies, and efforts are being made by countries to do so, in contrast, crime is regarded as one of the most negative factors that impede such efforts for the development. Moreover, as money laundering is one of the most important factors hindering the development process because of its high interrelatedness with social activities of various types, primarily the economical ones, it has become a necessity to highlight them. As this crime has economic, social and political risks at the international and national levels, that is to say, the scope of its negative impact is not limited to one country, but its impact has a global dimension.
مجلد 02 العدد 02
Keywords: جريمة- تبييض الأموال - خلية معالجة الاستعلام المالي- العقوبات الأصلية- العقوبات التكميلية.; Crime- money laundering -Financial query processing cell - The original penalties-the complementary penalties.